2020
DOI: 10.1371/journal.pgen.1009187
|View full text |Cite
|
Sign up to set email alerts
|

Folliculin variants linked to Birt-Hogg-Dubé syndrome are targeted for proteasomal degradation

Abstract: Germline mutations in the folliculin (FLCN) tumor suppressor gene are linked to Birt-Hogg-Dubé (BHD) syndrome, a dominantly inherited genetic disease characterized by predisposition to fibrofolliculomas, lung cysts, and renal cancer. Most BHD-linked FLCN variants include large deletions and splice site aberrations predicted to cause loss of function. The mechanisms by which missense variants and short in-frame deletions in FLCN trigger disease are unknown. Here, we present an integrated computational and exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 109 publications
0
15
0
Order By: Relevance
“…Although targeting Hsp110 to stabilize ASPA C152W resulted in the accumulation of insoluble protein, it might still be a relevant target for other ASPA variants that are at least partially soluble and contain residual activity. Accordingly, Hsp110 should be explored further as a potential therapeutic target to decrease the degradation of ASPA and other misfolded proteins, possibly using a recently developed inhibitor of Hsp110 [ 81 ], to potentially avoid or diminish the development of Canavan disease and other protein misfolding disorders such as Lynch syndrome or Birt-Hogg-Dubé syndrome [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although targeting Hsp110 to stabilize ASPA C152W resulted in the accumulation of insoluble protein, it might still be a relevant target for other ASPA variants that are at least partially soluble and contain residual activity. Accordingly, Hsp110 should be explored further as a potential therapeutic target to decrease the degradation of ASPA and other misfolded proteins, possibly using a recently developed inhibitor of Hsp110 [ 81 ], to potentially avoid or diminish the development of Canavan disease and other protein misfolding disorders such as Lynch syndrome or Birt-Hogg-Dubé syndrome [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is well established that certain missense mutations may cause protein destabilization and degradation (Stein et al, 2019), and that this is the underlying molecular mechanism for a number of hereditary diseases, including cystic fibrosis, phenylketonuria and various cancer predisposition disorders (Abildgaard et al, 2019; Ahner et al, 2007; Arlow et al, 2013; Canaff et al, 2012; Clausen et al, 2020; Gersing et al, 2021; Pey et al, 2007; Scheller et al, 2019). Here, we add hereditary megaloblastic anemia, linked to germline DHFR variants, to this list.…”
Section: Discussionmentioning
confidence: 99%
“…Rarer BHD-linked FLCN mutations result in the expression of missense and short in-frame deletions variants. Recent studies have shown that the loss-of-function associated with these variants is due to proteasomal degradation of FLCN proteins ( Nahorski et al, 2011 ; Clausen et al, 2020 ). FLCN is considered a tumor suppressor, following the Knudson “second hit” model, since somatic mutation or loss of heterozygosity of the non-affected allele has been observed in BHD-associated renal tumors and in animal models ( Schmidt and Linehan, 2018 ).…”
Section: Introductionmentioning
confidence: 99%